Game-based learning for marine resource management: Reflections on using games in the Bachelor of Science in Fisheries and Aquaculture - Weines, Jørn (UiT The Arctic University of Norway, 2021)
This dissertation is a case-study of the development and introduction of game-based learning in the Bachelor of Science in Fisheries and Aquaculture at the Norwegian College of Fishery Science. The use of games for learning has long traditions, but is currently receiving increased attention from scholars in light of the increased focus on active learning in higher education institutions. The Norwegian College of Fishery Science at UiT The Arctic University of Norway established the SimFish-project to develop innovative interdisciplinary learning in fisheries and aquaculture. This thesis presents research produced in connection with this project, focusing on the case of game-based instruction loops for marine resource management in the Bachelor of Science in Fisheries and Aquaculture. The case study is interdisciplinary, drawing on social science fisheries studies, active learning, game-based learning, and historical game studies. The included papers deal with different facets of these fields. The main aim in this thesis is to investigate how the underlying concepts of sustainable fisheries governance and core learning objectives in marine resource management can be integrated in game-based learning activities, and study the impacts the introduction of games as educational practice have had in the study program. The main focus of analysis is the qualitative data collected from students after game sessions, and an end of program evaluation for graduates of the program. The results show that the game-based instruction loops have served to engage the students, and contributed to the attainment of the learning outcomes in marine resource management. The games have been both a positive learning experience, and provided simulated experience that the students find relevant for the real-world seafood industry and understanding issues related to sustainable fisheries management. The games have offered opportunities for the students to practice 21st Century skills, but the data collection has not been specific enough to ...